Retro-psoas appendix: A rare atypical position of the appendix tip Radiological Images and Review of Literature - Afzal, Muniba; Al-Yahri, Omer; Musthafa, Shameel; ALI, SYED MUHAMMAD; Mohamed Said Ghali, (European Journal of Applied Sciences, 2022)
The vermiform appendix is considered by most to be a vestigial organ. Its importance in surgery results only from its propensity for inflammation. The tip of the appendix may lie in various locations, of which, the most common is retrocecal within the peritoneal cavity. Atypical locations of the appendix have often been reported in the literature. We report an unusual location of the appendix in the right retro-psoas muscle space.